Categorization of New Religious Movements in American Print Media - Driel, Barry van (Sociological analysis, 1988)
Barend van Driel, James T. Richardson; Categorization of New Religious Movements in American Print Media, Sociology of Religion, Volume 49, Issue 2, 1 July 1988